Hearing impairment and higher education: perceptions of students and employees in a Brazilian Public Institution (Research, Society and Development, 2020)
The aim of this study was to identify the perceptions of the hearing impaired students and the Accessibility Center employees of a Public Higher Education Institution regarding the policies and actions of accessibility and permanence in the education offered in the institution in which they are linked. Also, to verify the association between the preferential linguistic modality of the hearing impaired students and their responses regarding the policies of accessibility and permanence in education in a Higher Education Institution. As well as to identify the architectural and communicational barriers that undermines the academic performance of these students. 14 hearing impaired students and 5 Accessibility Center employees of a Higher Education Institution participated in this study. The data collection occurred through an online questionnaire. It was verified that the two groups did not obtained similar perceptions regarding accessibility and permanence. There was no statistical difference between the linguistic modality and the responses regarding accessibility and permanence in higher education. The students report as main architectural and communication barriers: classroom, learning disability and difficulty in following the contents during classes. This research verified that there is a divergence between students and employees´ perceptions. Regardless of the preferred linguistic modality, students with hearing impairment have the same perceptions regarding accessibility and permanence in higher education. The architectural and communicational barriers were identified in the studied sample.